The impact of chikungunya fever on pregnancy: a systematic review / Impactos da febre da chikungunya na gestação: uma revisão sistemática da literatura - Cabral, Symara Abrantes Albuquerque de Oliveira (2021)
ABSTRACT Introduction: Chikungunya virus (CHIKV) was introduced in Brazil in 2015, with occasional occurrences that soon spread in a large part of the country. The disease, in view of its long-standing consequences for the affected individuals, brought intense public health concerns. Pregnancy is a period of intense organic changes and may be affected in the case of CHIKV infection. However, the maternal and fetal impacts of CHIKV virus infection during pregnancy are not fully understood. Objective: To describe the maternal and fetal impacts following a CHIKV infection during pregnancy. Method: A systematic narrative review of the literature was performed in order to establish a compendium of information about the impacts of CHIKV infection during pregnancy. Results: is a potential for placental transfer of infection from the pregnant woman to the fetus, especially when it occurs close to delivery, as well as fetal manifestations, including with imminent severity. No complications were reported for pregnant women after CHIKV infection. Conclusion: Potential severity for the fetus precedes a need for preventive investments, especially in prenatal care. Keywords: Chikungunya virus, CHIKV, Pregnancy, Chikungunya feverÂ RESUMOIntrodução: o vírus da chikungunya (CHIKV) foi introduzido no Brasil em 2015, com ocorrências pontuais que logo se disseminaram em grande parte do país. A doença, diante de suas consequências para o indivíduo acometido, sobretudo í  longo prazo, trouxe intensas complicações para saúde pública. É consenso a ocorrência de morbimortalidade decorrente da doença e, sendo a gestação um período de intensas mudanças orgânicas, importante se faz considerar o questionamento: quais os impactos maternos e fetais da infecção pelo vírus da chikungunya na gestação? Objetivo: descrever os impactos maternos e fetais decorrentes da infecção pelo CHIKV. Método: revisão sistemática da literatura de modo a estabelecer um compêndio de informações acerca dos impactos da CHIKV na gravidez. Resultados: observou-se potencial de transferência placentária da gestante para o feto, sobretudo quando a infecção ocorre próximo ao parto, bem como manifestações fetais, inclusive com gravidade. Não foram descritas complicações í  mulher grávida infectada pelo CHIKV. Conclusões: potencial de gravidade para o feto precede uma necessidade de investimentos preventivos, sobretudo no pré-natal.Palavras chave: Vírus chikungunya, CHIKV, Gravidez, Febre de chikungunya Introduct